NAVIGATING NEUTRALITY: INDONESIA’S LEGAL DILEMMA OVER INNOCENT PASSAGE IN THE INDO-PACIFIC POWER RIVALRY - Kadiaman, Joseph Jubata; Gaudensia Diana KF; Fadilah, Ahmad (Rechtsregel : Jurnal Ilmu Hukum, 2025)
This study addresses Indonesia’s strategic dilemma in maintaining neutrality and safeguarding maritime sovereignty amid intensifying geopolitical competition in the Indo-Pacific, particularly regarding the right of innocent passage through the Indonesian Archipelagic Sea Lanes (ALKI). The research is positioned within the context of evolving regional security dynamics, the rise of alliances such as AUKUS, and Indonesia’s constitutional mandate for an independent and active foreign policy. Employing a normative juridical approach, the study analyzes UNCLOS 1982, Indonesian maritime legislation, and relevant international relations theories, supported by case studies and comparative analysis with other archipelagic and neutral states. The findings reveal that, while Indonesia’s reliance on ASEAN-led diplomacy faces increasing limitations, harmonizing domestic regulations with UNCLOS, strengthening maritime surveillance, and advancing confidence-building measures are essential for upholding neutrality and regional stability. The research concludes that Indonesia’s proactive legal and policy strategies-grounded in clear legal frameworks and supported by preventive diplomacy-are crucial for balancing international obligations and national interests, ensuring ALKI serves as a bridge of peace in the Indo-Pacific.